In Vivo Dark-Field Radiography for Early Diagnosis and Staging of Pulmonary Emphysema. Issue 7 (July 2015) - Hellbach, Katharina; Yaroshenko, Andre; Meinel, Felix G.; Yildirim, Ali Ö.; Conlon, Thomas M.; Bech, Martin; Mueller, Mark; Velroyen, Astrid; Notohamiprodjo, Mike; Bamberg, Fabian; Auweter, Sigrid; Reiser, Maximilian; et al.
Abstract : Objectives: The aim of this study was to evaluate the suitability of in vivo x-ray dark-field radiography for early-stage diagnosis of pulmonary emphysema in mice. Furthermore, we aimed to analyze how the dark-field signal correlates with morphological changes of lung architecture at distinct stages of emphysema. Materials and Methods: Female 8- to 10-week-old C57Bl/6N mice were used throughout all experiments. Pulmonary emphysema was induced by orotracheal injection of porcine pancreatic elastase (80-U/kg body weight) (n = 30). Control mice (n = 11) received orotracheal injection of phosphate-buffered saline. To monitor the temporal patterns of emphysema development over time, the mice were imaged 7, 14, or 21 days after the application of elastase or phosphate-buffered saline. X-ray transmission and dark-field images were acquired with a prototype grating-based small-animal scanner. In vivo pulmonary function tests were performed before killing the animals. In addition, lungs were obtained for detailed histopathological analysis, including mean cord length (MCL) quantification as a parameter for the assessment of emphysema. Three blinded readers, all of them experienced radiologists and familiar with dark-field imaging, were asked to grade the severity of emphysema for both dark-field and transmission images. Results: Histopathology and MCL quantification confirmed the introduction of different stages of emphysema, which could be clearly visualized and differentiated on the dark-field radiograms, whereas early stages were not detected on transmission images. The correlation between MCL and dark-field signal intensities ( r = 0.85) was significantly higher than the correlation between MCL and transmission signal intensities ( r = 0.37). The readers' visual ratings for dark-field images correlated significantly better with MCL ( r = 0.85) than visual ratings for transmission images ( r = 0.36). Interreader agreement and the diagnostic accuracy of both quantitative and visual assessment were significantly higher for dark-field imaging than those for conventional transmission images. Conclusions: X-ray dark-field radiography can reliably visualize different stages of emphysema in vivo and demonstrates significantly higher diagnostic accuracy for early stages of emphysema than conventional attenuation-based radiography. Abstract : Supplemental digital content is available in the text.